Topological point defects in nematic liquid crystals - Kleman, M.; Lavrentovich, O. D. (Philosophical magazine (Abingdon, England), 2006)
Point defects in nematics, also called hedgehogs, are topological entities that have no equivalent in ordered atomic solids, despite the homonymy. They have been the subject of intense experimental and, above all, theoretical (analytical and computational) investigations in the last thirty years. They are present in bulk specimens and at the specimen boundaries. This review article stresses the importance of the core structure of the defect, the possibility of it splitting into a disclination loop, and boundary conditions, as well as taking stock of the recent advances on point defects in nematic colloidal suspensions. An important topic is the formation of strings between opposite hedgehogs (radial and hyperbolic), and their role in the dynamic properties of nematics.